Declining trends in some sexually transmitted diseases in Belgium between 1983 and 1989. Issue 5 (October 1991) - Walckiers, D; Piot, P; Stroobant, A; Van der Veken, J; Declercq, E
Abstract : OBJECTIVE--To examine trends in some sexually transmitted diseases in Belgium and to discuss them in the light of the European background. DESIGN--Analysis of the time trends of C trachomatis and N gonorrhoeae infections diagnosed by a network of microbiological laboratories, and of male urethritis diagnosed by a network of general practitioners. SETTING--Belgium. SUBJECTS--Reports of C trachomatis and N gonorrhoeae infections by a network of microbiological laboratories, and of male urethritis by a network of general practitioners, to the Institute of Hygiene and Epidemiology. RESULTS--Whereas an increase in the number of C trachomatis infections, more pronounced among women, was observed up to 1986, a small decrease has been observed afterwards in males. The mean number of chlamydial infections per laboratory and per year was 4.2 in 1983, 15.7 in 1986 and 13.9 in 1989. A decrease in the number of N gonorrhoeae infections, more pronounced among men, has been observed. The mean number of cases of gonorrhoea per laboratory and per year was 10.9 in 1983 and only 2.2 in 1989. The same declining trend has been observed in another surveillance programme of male urethritis, based on a network of general practitioners. The number of cases of male urethritis per 100 patient encounters went down from 0.06 in 1982-3 to 0.04 in 1988-9. CONCLUSION--The declining trend in Western Europe in incidence of gonococcal infections and of urethritis in men is also occurring in Belgium, but genital chlamydial infections remain an important public health problem.